Sweet on you - Wade, Becky (Wade, Becky. Bradford Sisters romance., 2019)
Britt and Zander have been best friends since they met thirteen years ago, and Zander has been in love with her all those years. When Zander's uncle dies of mysterious causes, he returns to Merryweather, Washington. As they work together to uncover his uncle's tangled past, will the truth of what lies between them come to light?